Evaluating the inhibitory priority of Bcl‐xL to Bad, tBid and Bax by using live‐cell imaging assay. Issue 11 (22nd April 2021) - Wu, Ge; Tu, Zhuang; Yang, Fangfang; Mai, Zihao; Chen, Hongce; Tang, Qiling; Ye, Xianxin; Wang, Kunhao; Wang, Xiaoping; Chen, Tongsheng
Abstract: Molecular regulatory network among the B cell leukemia‐2 (Bcl‐2) family proteins is a research hotspot on apoptosis. The inhibitory priority of anti‐apoptotic Bcl‐2 family proteins (such as Bcl‐xL) to pro‐apoptotic Bcl‐2 family proteins (such as Bad, tBid and Bax) determines the outcome of their interactions. Based on over‐expression model system, we here evaluate the inhibitory priority of Bcl‐xL to Bad, tBid and Bax by using live‐cell imaging assay on cell viability. Fluorescence images of living cells co‐expressing CFP‐Bcl‐xL and YFP‐Bad or YFP‐tBid or YFP‐Bax showed that Bcl‐xL markedly inhibited Bad/tBid/Bax‐mediated apoptosis, revealing that Bcl‐xL inhibits the proapoptotic function of Bad, tBid and Bax. In the case of equimolar co‐expression of Bad and CFP‐Bcl‐xL, the inhibition of Bcl‐xL on tBid/Bax mediate‐apoptosis was completely relieved. Moreover, co‐expression of tBid‐P2A‐CFP‐Bcl‐xL significantly relieved the inhibition of Bcl‐xL on the pro‐apoptotic ability Bax, suggesting that Bcl‐xL preferentially inhibits the pro‐apoptotic ability of Bad over tBid, subsequently to Bax. Abstract :